PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH DI KABUPATEN LUWU TIMUR - Dianti, Ella; Sahade; Syachbrani, Warka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of Human Resources (HR) competency and the implementation of Government Accounting Standards (SAP) on the quality of local government financial reports in the East Luwu Regency Government. This study was motivated by the continued discovery of several weaknesses in regional financial management even though East Luwu Regency has obtained an Unqualified Opinion (WTP) from the Supreme Audit Agency (BPK). In addition, some financial employees do not have adequate accounting education backgrounds, which has the potential to affect the quality of financial report preparation. This study uses compliance theory as a theoretical basis, explaining that apparatus compliance with applicable rules and standards can affect the quality of task implementation, including in the preparation of financial reports. The research method used is quantitative with the analysis unit of financial employees in several Regional Apparatus Organizations (OPD) in East Luwu Regency. The research sample amounted to 62 respondents who were determined using a saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination tests. The results of the study indicate that HR competency has a significant effect on the quality of local government financial reports with a regression coefficient of -0.212 and a significance value of 0.001. Meanwhile, SAP implementation has a positive and significant effect on the quality of financial reports with a regression coefficient of 0.112 and a significance value of 0.002. Simultaneously, HR competency and SAP implementation have a significant effect on the quality of local government financial reports. The Adjusted R² value of 0.292 indicates that both variables are able to explain 29.2% of the variation in the quality of financial reports, while 70.8% is influenced by other factors outside the study.